BEYOND TRANSACTION: A CONCEPTUAL FRAMEWORK FOR MARKETING MANAGEMENT THROUGH THE ETHICAL LENS OF TASAWWUF - Kusumohadiati, Hanny; Aulia, Sulvy Mutiara; Agustini, Rooswanti Putri Adi; Tutuko, Bambang; Kustyadji, Gatot; Rensy, Milla (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
Contemporary marketing management, often predicated on the stimulation of limitless consumer desire, presents a fundamental tension with the principles of Tasawwuf (Sufism), an Islamic spiritual discipline aimed at the purification of the self and the cultivation of virtue. This paper addresses a significant gap in the literature by developing a novel conceptual framework that integrates the ethical-spiritual tenets of Tasawwuf into the core strategic and tactical domains of marketing. Employing a qualitative systematic literature review, this study first synthesizes the foundational concepts of modern marketing management and the key socio-economic virtues of Tasawwuf. The subsequent analysis reveals a profound ontological conflict between the marketing paradigm's definition of the human as a 'consumer' and Tasawwuf's conception of the human as a servant of God ('abd) and steward (khalifah). Building on this, the paper proposes a reconstructed marketing mix (7Ps) where each element is re-envisioned through guiding Sufi principles. 'Product' is reconceptualized as a trust (Amanah) demanding excellence (Ihsan); 'Price' is governed by justice ('Adl); 'Promotion' is guided by truthfulness (Sidq); and 'People' are viewed as a community of service (Khidmah). The framework posits that the cultivation of spiritual consciousness (ruhaniyah) within the organization is the mediating factor that enables the authentic application of these principles. This study contributes a new, holistic paradigm for marketing that shifts the objective from transactional value-exchange to the facilitation of holistic human well-being (falah), offering a robust, ethically grounded alternative to conventional models that is relevant not only within Islamic contexts but also to the global discourse on purpose-driven and sustainable business.